miRNA-141 Induced Pyroptosis in Intervertebral Disk Degeneration by Targeting ROS Generation and Activating TXNIP/NLRP3 Signaling in Nucleus Pulpous Cells - Xu, Qiaolong; Xing, Hongyuan; Wu, Jiaqi; Chen, Weishan; Zhang, Ning (Frontiers in Cell and Developmental Biology, 2020)
The role and mechanism of pyroptosis in intervertebral disc (IVD) degeneration are unclear. MicroRNAs (miRNAs) regulate the viability and function of nucleus pulposus cells (NPCs) in IVDs and are related to pyroptosis. We performed microarray analyses of normal and degenerated NP to assess the role of pyroptosis and identify key miRNAs in IVD degeneration. We also evaluated the underlying mechanism of miRNA-mediated pyroptosis in NPCs. In addition, we demonstrated the preventative effects of miRNAs on IVD degeneration in a rat model. The levels of the pyroptosis-related proteins cleaved caspase-1, N-terminal gasdermin D, interleukin (IL)-1β, and IL-18 in the degenerative NP were significantly higher than those in the normal NP. miRNA-141 was significantly upregulated in the degenerated NP. miR-141 mimic suppressed the matrix synthesis function of NPCs. By contrast, reactive oxygen species (ROS) generation, and the expression of TXNIP and NLRP3 were significantly downregulated by an miR-141 inhibitor. Furthermore, the miRNA-141 inhibitor prevented the degeneration of IVDs in vivo. Our findings suggest that miRNA-141 induces pyroptosis and extracellular matrix catabolism in NPCs by increasing ROS generation and activating TXNIP/NLRP3 signalling. miRNA-141-regulated pyroptosis may be a novel therapeutic target for IVD degeneration.